Plasminogen activation and cancer - Danø, Keld; Behrendt, Niels; Høyer-Hansen, Gunilla; Johnsen, Morten; Lund, Leif R.; Ploug, Michael; Rømer, John (Thrombosis and Haemostasis, 2005)
Breakdown of the extracellular matrix is crucial for cancer invasion and metastasis. It is accomplished by the concerted action of several proteases, including the serine protease plasmin and a number of matrix metalloproteases. The activity of each of these proteases is regulated by an array of activators, inhibitors and cellular receptors. Thus, the generation of plasmin involves the pro-enzyme plasminogen, the urokinase type plasminogen activator uPA and its pro-enzyme pro-uPA, the uPA inhibitor PAI-1, the cell surface uPA receptor uPAR, and the plasmin inhibitor α2-antiplasmin. Furthermore, the regulation of extracellular proteolysis in cancer involves a complex interplay between cancer cells and non-malignant stromal cells in the expression of the molecular components involved. For some types of cancer, this cellular interplay mimics that observed in the tissue of origin during non-neoplastic tissue remodelling processes. We propose that cancer invasion can be considered as uncontrolled tissue remodelling. Inhibition of extracellular proteases is an attractive approach to cancer therapy. Because proteases have many different functions in the normal organism, efficient inhibition will have toxic side effects. In cancer invasion, like in normal tissue remodelling processes, there appears to be a functional overlap between different extracellular proteases. This redundancy means that combinations of protease inhibitors must be used. Such combination therapy, however, is also likely to increase toxicity. Therefore for each type of cancer, a combination of protease inhibitors that is optimised with respect to both maximal therapeutic effect and minimal toxic side effects need to be identified.
Keywords: Cancer invasion; plasminogen activation; matrix degradation; tissue remodelling; cancer therapy